MODERASI MANAJEMEN RISIKO PADA HUBUNGAN HUMAN RESOURCE MANAGEMENT DAN KINERJA DI INDUSTRI KELAPA SAWIT - Wendi Amsuri Nasution (Smart Education, 2026)
Abstract: Human Resource Management (HRM) plays a strategic role in improving organizational performance through effective workforce management. However, its effectiveness also depends on an organization's capability to manage operational risks. This study develops a Risk Management moderation model by examining the relationship between Human Resource Management and Employee Performance as a representation of performance in the palm oil industry. A post positivist paradigm with a quantitative explanatory approach was employed at PT Perkebunan Nusantara IV Regional 2 Pulu Raja Estate and Palm Oil Mill. Data were collected from 193 permanent employees selected through proportionate stratified random sampling from a population of 370 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that Human Resource Management (β = 0.554, p < 0.001) and Operational Risk Readiness (β = 0.447, p < 0.001) have positive and significant effects on Employee Performance. Moreover, Operational Risk Readiness significantly moderates the relationship between Human Resource Management and Employee Performance (β = 0.132, p = 0.003). The model demonstrates satisfactory explanatory and predictive capability (R² = 0.522; Q² = 0.417; SRMR = 0.048). These findings highlight the importance of integrating Human Resource Management and Risk Management to improve Employee Performance in the palm oil industry.